RUNX regulated immune-associated genes predicts prognosis in breast cancer - Fu, Jingyue; Sun, Handong; Xu, Feng; Chen, Rui; Wang, Xinyang; Ding, Qiang; Xia, Tiansong (Frontiers in Genetics, 2022)
Background Breast cancer is the most common malignant tumor in women. RUNX family has been involved in the regulation of different carcinogenic processes and signaling pathways with cancer, which is closely related to immunity and prognosis of various tumors, and also plays an important role in the development and prognosis of breast cancer. Methods We discovered the expression of RUNX family through GEPIA Dataset and then evaluated the relationship between RUNX family and immune-related genes and the prognosis of breast cancer through analyzing TCGA database. A prognostic model was established and verified via cox proportional hazards regression model using R packages. We evaluate the accuracy of the prognostic model by Kaplan-Meier curves and receiver operating characteristic (ROC) curve. Additionally, we obtained the relationship between the RUNX family and immune infiltration by TIMER database. Finally, the dual luciferase reporter assay was used to verify the regulation of RUNX3 on potential target genes ULBP2 and TRDV1, and the effects of ULBP2 and TRDV1 on the growth of breast cancer cells were explored by CCK-8, colony formation and wound healing assays. Results We screened out RUNX family-regulated immune-related genes associated with the prognosis of breast cancer. These predictors included PSME2, ULBP2, IL-18, TSLP, NPR3, TRDV1. Then a prognosis-related risk score model was built using the independent risk factors to provide a clinically appropriate method predicting the overall survival (OS) probability of the patients with breast cancer. In addition, a further research was made on the functions of high risk immune gene ULBP2 and low risk immune gene TRDV1 which regulated by RUNX3, the results show that down-regulation of ULBP2 suppressed breast cancer cell proliferation and TRDV1 have the opposite functions. The prognostic model we constructed could promote the development of prognostic, and was associated with lower immune infiltration. Conclusion The expression of RUNX family is closely related to the prognosis of breast cancer. At the same time, RUNX family could modulate the functions of immune-related genes, and affects the development and prognosis of breast cancer. These immune-related genes regulated by RUNX family could be promising prognostic biomarkers and therapeutic targets in breast cancer.